Assessing the Attitude and Practices of Dental Surgeons Towards Periodontal Health After the COVID-19 Outbreak - Moi Kato; Shalabh Mehrotra; Zoya Chowdhary; Monalisa Mosang; Abdul Waris (Association of Support to Oral Health Research (APESB), 2024)
Objective: To assess the orientation of dental practitioners in understanding the probable relationship between COVID-19 and periodontal infection and the measures they took toward periodontal health during the pandemic. Material and Methods: A cross-sectional questionnaire-based survey was conducted, including registered dentists in Moradabad. The questionnaire provided was a self-administered, closed-ended questionnaire with 26 questions, shared via an online survey link utilizing Google Forms. The data collected was tabulated and statistically evaluated. Results: The participants implemented many preventive measures in their daily lives against COVID-19, such as hand washing, frequent hand sanitization, face shields, mouth masks, social distancing not, being in overcrowded places, using HEPA filters and different combinations of protective measures against COVID-19. 82.23% of participants learned from the official websites of organizations like the Ministries of Health, WHO, and professional organizations about COVID-19. Conclusion: Most participants endorsed oral hygiene measures and the use of mouthwashes by their patients, yet a significant number of dental surgeons needed to be made aware of a probable correlation between COVID-19 infection and chronic periodontitis.